Reviewing the Prospective Pharmacological Potential of Isothiocyanates in Fight against Female-Specific Cancers - Shoabib, Shoaib; Khan, Farheen Badrealam; Alsharif, Meshari A.; Malik, M Shaheer; Ahmed, Saleh A; Jamous, Yahya F; Uddin, Shahab; Tan, Ching Siang; Ardianto, Chrismawan; Tufail, Saba; Long, Chiau Ming *; Yusuf, Nabiha; et al. (MDPI, 2023)
Gynecological cancers are the most commonly diagnosed malignancies in females worldwide. Despite the advancement of diagnostic tools as well as the availability of various therapeutic interventions, the incidence and mortality of female-specific cancers is still a life-threatening issue, prevailing as one of the major health problems worldwide. Lately, alternative medicines have garnered immense attention as a therapeutic intervention against various types of cancers, seemingly because of their safety profiles and enhanced effectiveness. Isothiocyanates (ITCs), specifically sulforaphane, benzyl isothiocyanate, and phenethyl isothiocyanate, have shown an intriguing potential to actively contribute to cancer cell growth inhibition, apoptosis induction, epigenetic alterations, and modulation of autophagy and cancer stem cells in female-specific cancers. Additionally, it has been shown that ITCs plausibly enhance the chemo-sensitization of many chemotherapeutic drugs. To this end, evidence has shown enhanced efficacy in combinatorial regimens with conventional chemotherapeutic drugs and/or other phytochemicals. Reckoning with these, herein, we discuss the advances in the knowledge regarding the aspects highlighting the molecular intricacies of ITCs in female-specific cancers. In addition, we have also argued regarding the potential of ITCs either as solitary treatment or in a combinatorial therapeutic regimen for the prevention and/or treatment of female-specific cancers. Hopefully, this review will open new horizons for consideration of ITCs in therapeutic interventions that would undoubtedly improve the prognosis of the female-specific cancer clientele. Considering all these, it is reasonable to state that a better understanding of these molecular intricacies will plausibly provide a facile opportunity for treating these female-specific cancers.